Enhanced Methane Production from Protein and Lipid-Rich Wastewater Using Powdered Oat Husk-Biochar - Pages-Diaz, J (John Wiley and Sons Ltd, 2024)
BACKGROUND: Due to the lower degradation and the potential inhibitory compounds present in slaughterhouse wastewater (SW), its industrial applications are often limited to methane production. This study investigated the combined effect of conductive material such as oat husk-biochar at different concentrations (0, 5, 10, 15, 20, 25 g L−1) and particle sizes (i.e., Powder Biochar (PB) (0.05–0.08 mm) vs. Granular Biochar (GB) (0.8–1.0 mm)) in the methane production, biodegradability, kinetic parameters, methanogenic activity and digestate quality of SW, using a multilevel factorial design. RESULTS: Experimental results showed that lower concentration (5, 10 g L−1) increased the methane yield up to 35% for PB and between 11 and 13% for GB compared to the control reactor. The total ammoniacal nitrogen concentrations in the digestate declined between 14% and 52% for all biochar dosages and particle sizes. PB improved the specific methanogenic activity of the biomass compared with GB, indicating that PB can support a well-balanced methanogenic community compared with GB inside the digester. The multiple response optimization process computed that 7.5 g L−1 of PB is optimal to increase the methane yield, the COD degradation efficiency and shorten the lag phase. On the other hand, doses higher than 15 g L−1 hinder methane generation. CONCLUSIONS: PB supplementation has significant potential to improve the anaerobic degradation of SW. The improvement is attributed to the higher specific surface area, contributing to better support and microbial activity. © 2024 Society of Chemical Industry (SCI). © 2024 Society of Chemical Industry (SCI).